A comprehensive review on mechanical properties of pultruded FRP composites subjected to long-term environmental effects. (15th June 2020) - Liu, TianQiao; Liu, Xing; Feng, Peng
Abstract: Pultruded fiber-reinforced polymer (FRP) composite is expected to be widely applied for civil infrastructures due to its advantages of lightweight, anti-corrosion, and industrial manufacturing. Its long-term performance has attracted increasing attentions from academia and industry. This paper presents a comprehensive review on experimental studies investigating the mechanical performance of pultruded FRP composites subjected to long-term environmental effects, including water/moisture, alkaline solutions, acidic solutions, low/high temperatures, ultraviolet radiation, freeze-thaw cycles, wet-dry cycles, and in situ environments. Over 1900 experimentally determined mechanical properties of FRP materials were collected, including tensile, compressive, flexural and shear strength and moduli. The reported test data were highly dispersed, and no uniform conclusions could be drawn from these data. Exposure to water and water-based solutions (alkaline and acidic solutions) had detrimental impacts on the mechanical properties of pultruded FRP materials, whereas other environmental effects induced various levels of degradation. The degradation mechanisms for each environmental effect were discussed, and the existing design approaches were presented. Based on the findings from this review, recommendations were proposed for future works. The database presented herein, which is the largest in the available literature, enables a comprehensive understanding of the degradation behavior of pultruded FRP composites. Moreover, this work can serve as a foundation for deriving predictive models for pultruded FRP materials exposed to long-term environmental effects.